The Importance Of Research And Development In The Syrian Pharmaceutical Industry - Hormuz, Noureddine; Ebraheem, Ola (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The Aim Of The Researcher Through This Study Is To Introduce The Importance Of Research And Development In An Industry Based On Scientific Research, Namely The Pharmaceutical Industry And The Extent Of The Contribution Of Scientific Research In The Discovery Of New Drugs And Activate The Contribution Of This Industry In The National Economy And Increase The Value Added Resulting From This Industry, And This Study Can Contribute To Support Pharmaceutical Companies Through The Results Of The Research And Development In The Syrian Pharmaceutical Industry, And Overcome The Weaknesses, Problems And Challenges Facing The Industry To Ensure The Increase Of The Industry’s Contribution To The National Economy, And The Study Found A Direct Relationship Between Research And Development T As An Influential Factor In Production And Activate The Role Of The Pharmaceutical Industry In The National Economy. هدف الباحث من خلال هذه الدراسة إلى التعريف بأهمية البحث والتطوير في صناعة أساسها البحث العلمي ،وهي صناعة الدواء ومدى مساهمة البحث العلمي في اكتشاف عقاقير جديدة وتفعيل مساهمة هذه الصناعة في الاقتصاد الوطني وزيادة القيمة المضافة الناتجة عن هذه الصناعة, ويمكن أن تساهم هذه الدراسة في دعم شركات الأدوية من خلال النتائج التي سيقدمها البحث، وتجاوز نقاط الضعف والمشكلات والتحديات التي تواجه هذه الصناعة بما يضمن زيادة مساهمة هذه الصناعة في الاقتصاد الوطني ،وتوصلت الدراسة إلى وجود علاقة طردية بين البحث والتطوير كعامل مؤثر في الإنتاج وتفعيل دور الصناعة الدوائية في الاقتصاد الوطني.